Modeling Natural Killer Cell Targeted Immunotherapies - Lopez-Lastra, Silvia; Di Santo, James P. (Frontiers in Immunology, 2017)
Animal models have extensively contributed to our understanding of human immunobiology and to uncover the underlying pathological mechanisms occurring in the development of diseases. However, mouse models do not reproduce the genetic and molecular complexity inherent in human disease conditions. Human immune system (HIS) mouse models that are susceptible to human pathogens and can recapitulate human hematopoiesis and tumor immunobiology provide one means to bridge the interspecies gap. Natural killer cells are the founding member of the innate lymphoid cell (ILC) family. They exert a rapid and strong immune response against tumor and pathogen-infected cells. Their anti-tumor features have long been exploited for therapeutic purposes in the context of cancer. In this review we detail the development of highly immunodeficient mouse strains and the models currently used in cancer research. We summarize the latest improvements in adoptive NK cell therapies and the development of novel NK cell sources. Finally we discuss the advantages of HIS mice to study the interactions between human NK cells and human cancers and to develop new therapeutic strategies.